The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1093/jnci/93.6.456
|View full text |Cite
|
Sign up to set email alerts
|

Scottish Adjuvant Tamoxifen Trial: a Randomized Study Updated to 15 Years

Abstract: Information from this study suggests that, if adjuvant tamoxifen is given to women with operable breast cancer, it need not be for more than 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
1
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(100 citation statements)
references
References 4 publications
2
92
1
5
Order By: Relevance
“…A drawback of this study was the relatively short period of tamoxifen treatment of the patients during 1 or 3 years, according to the original setting up of the trial. Recent studies suggest that tamoxifen should be given for longer periods (probably 5 years or more) (Early Breast Cancer Trialist's Collaborative Group, 1998;Fischer et al, 2001;Steward et al, 2001). In our marker study about 50% of the patients received tamoxifen for only 1 year and 74 patients did not receive tamoxifen treatment at all.…”
Section: Discussionmentioning
confidence: 99%
“…A drawback of this study was the relatively short period of tamoxifen treatment of the patients during 1 or 3 years, according to the original setting up of the trial. Recent studies suggest that tamoxifen should be given for longer periods (probably 5 years or more) (Early Breast Cancer Trialist's Collaborative Group, 1998;Fischer et al, 2001;Steward et al, 2001). In our marker study about 50% of the patients received tamoxifen for only 1 year and 74 patients did not receive tamoxifen treatment at all.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the patients received an adjuvant therapy with oral 5-FU and TAM. TAM is the gold standard for adjuvant endocrine therapy after breast cancer surgery (Early Breast Cancer Trialists' Collaborative Group, 1998;Stewart et al, 2001). However, oral 5-FU as adjuvant therapy is not popular in the USA and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, a recent clinical trial found that the beneficial effect of 5 years of adjuvant tamoxifen persisted after 15 years of follow-up in postmenopausal women. 23 This is important because the oldest old are living longer than ever before. 24 The average life expectancy of healthy American women is 9.6 years for 85 year olds, 6.8 years for 90 year olds, and 4.8 years for 95 year olds.…”
Section: Discussionmentioning
confidence: 99%